2018
DOI: 10.1038/s41598-018-22250-8
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-induced caveolin-1 expression promotes T-DM1 drug efficacy in breast cancer cells

Abstract: Trastuzumab emtansine (T-DM1) is an antibody drug conjugate (ADC) that was recently approved for the treatment of HER-2-positive metastatic breast cancer. The drug sensitivity of ADCs depends mainly on the internalization efficiency of the drug. Caveolin-1 was shown to promote T-DM1 internalization and enhance drug sensitivity. Whether caveolin-1 can be overexpressed to improve T-DM1 efficacy is interesting and has the potential for clinical application. In this study, diabetes drug metformin was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity where their sensitivity to metformin was dependent on CAV1 expression and CAV1 was required to induce AMPK phosphorylation and the increase in the AMP/ATP ratio [196]. Metformin induces CAV1 expression [197], which in return increases clinical efficacy of drug delivery (trastuzumab emtansine) in breast cancer cells [198]. Sulphonylureas on the other hand increase insulin release by blocking K ATP channels [199].…”
mentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity where their sensitivity to metformin was dependent on CAV1 expression and CAV1 was required to induce AMPK phosphorylation and the increase in the AMP/ATP ratio [196]. Metformin induces CAV1 expression [197], which in return increases clinical efficacy of drug delivery (trastuzumab emtansine) in breast cancer cells [198]. Sulphonylureas on the other hand increase insulin release by blocking K ATP channels [199].…”
mentioning
confidence: 99%
“…Chung and colleagues (26) suggested that CAV1 promotes chemosensitivity to T-DM1, whereas others, on the contrary, reported that the acquisition of TDM1 resistance is due to deficient cleavage of T-DM1 in CAV1-associated endosomes (28). In favor of a role of CAV1 in promoting T-DM1 sensitivity, increased CAV1 expression by metformin was shown to induce T-DM1 internalization and subsequent cytotoxicity (27). Our data strongly support the concept of a dependence on vesicular, raft-associated CAV1 for efficient T-DM1 cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypoxia may augment ligand-independent EGFR signaling by increased dimerization and prolonged activation in caveolin-1 (CAV1)-associated membrane domains, further leading to enhanced tumor cell proliferation and invasiveness (21). Hypoxia was shown to downregulate membrane protein internalization through a mechanism that involved CAV1 (22), and other studies suggest that HER2 homodimers codistribute with cholesterol-rich membrane raft domains and an involvement of caveolae-dependent mechanisms in the regulation of HER2 trafficking (23)(24)(25)(26)(27)(28). Importantly, the possible link between hypoxia, HER2 internalization, and T-DM1 resistance remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The phase III EMILIA trial showed trastuzumab emtansine, an Ab conjugate, significantly prolonged the PFS and OS in metastatic breast cancer patients. Metformin promotes trastuzumab emtansine drug efficacy through inducing caveolin‐1 expression in breast cancer . As for some HER2‐positive breast carcinomas patients after trastuzumab treatment, lapatinib was usually used to inhibit cancer progression.…”
Section: Combination Of Metformin With Antibodiesmentioning
confidence: 99%
“…Metformin promotes trastuzumab emtansine drug efficacy through inducing caveolin-1 expression in breast cancer. 57 As for some HER2-positive breast carcinomas patients after trastuzumab treatment, lapatinib was usually used to inhibit cancer progression. Metformin could be a clinically useful candidate of delaying or treating lapatinib resistance by inactivating mTOR and decreasing p70S6K1 activity.…”
Section: Combination Of Metformin With Trastuzumabmentioning
confidence: 99%